Job Burnout in the Performance of Village Health Volunteers in Health Region 4 - มาลา มนัสพงษ์ (Journal of Health Science of Thailand, 2021)
The objective of this study was to assess demographic characteristics, work-related data, job satisfaction, job burnout, associated factors, and opinions on the management of job burnout among the village health volunteers in the Public Health Region 4. The descriptive study was conducted among the 1,074 village health volunteers selected by simple random sampling. The questionnaire was the instrument for collecting data on demographic characteristics, work-related data, job satisfaction, job burnout, related factors, and opinions on job burnout management. The internal consistency reliability and validity of the questionnaire were 0.83, 0.73 and 0.87 respectively. Data were analyzed by descriptive statistics consisted of frequency, percentage, mean, and standard deviation; moreover, inferential statistics consisted of t-test, one-way ANOVA, Pearson’s correlation, and multiple logistic regression. It was found that the village health volunteers had job burnout in an overview with a mean of 13.18 ((SD=10.64), 90.40% with low level emotional exhaustion, 75.14% with low level cynicism, and 51.21% with high level reduction of personal success. Job burnout was observed in 5.03% of the them. The results indicated that various factors related to job burnout included those who having congenital disease, working in the urban or semi-urban or rural community, having age over 60 years, graduated at least a bachelor degree, no smoking, no supported by the local governments, no counselor while facing problems, and low satisfaction of career progress, workload, job stability, compensation and welfare, and overall work. Some village health volunteers had a high-level of job burnout; meanwhile, most of them had a high-level of reduced personal success. The finding dentified many factors related to job burnout which should be presented to policymakers in order to be used as a guideline to prevent and reduce job burnout.